Organic molecules with inverted singlet-triplet gaps - Li, Jie; Li, Zhi; Liu, Hui; Gong, Heqi; Zhang, Jincheng; Yao, Yali; Guo, Qiang (Frontiers in Chemistry, 2022)
According to Hund's multiplicity rule, the energy of the lowest excited triplet state (T1) is always lower than that of the lowest excited singlet state (S1) in organic molecules, resulting in a positive singlet-triplet energy gap (ΔEST). Therefore, the up-converted reverse intersystem crossing (RISC) from T1 to S1 is an endothermic process, which may lead to the quenching of long-lived triplet excitons in electroluminescence, and subsequently the reduction of device efficiency. Interestingly, organic molecules with inverted singlet-triplet (INVEST) gaps in violation of Hund's multiplicity rule have recently come into the limelight. The unique feature has attracted extensive attention in the fields of organic optoelectronics and photocatalysis over the past few years. For an INVEST molecule possessing a higher T1 with respect to S1, namely a negative ΔEST, the down-converted RISC from T1 to S1 does not require thermal activation, which is possibly conducive to solving the problems of fast efficiency roll-off and short lifetime of organic light-emitting devices. By virtue of this property, INVEST molecules are recently regarded as a new generation of organic light-emitting materials. In this review, we briefly summarized the significant progress of INVEST molecules in both theoretical calculations and experimental studies, and put forward suggestions and expectations for future research.